2021
DOI: 10.1128/msystems.00518-21
|View full text |Cite
|
Sign up to set email alerts
|

Species-Level Resolution of Female Bladder Microbiota from 16S rRNA Amplicon Sequencing

Abstract: Accurate species-level identification from culture-independent techniques is of importance for microbial niches that are less well characterized, such as that of the bladder. 16S rRNA amplicon sequencing, a common culture-independent way to identify bacteria, is often critiqued for lacking species-level resolution. Here, we extensively evaluate classification schemes for species-level bacterial annotation of 16S amplicon data from bladder bacteria.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…These studies consistently demonstrated that the choice of the 16S rRNA primer set can significantly influence the analysis of microbiota diversity and composition. Apart from a recent study evaluating the female urobiome ( Hoffman et al., 2021 ), similar studies for urinary microbiota profiling are lacking. As reviewed by Cumpanas et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies consistently demonstrated that the choice of the 16S rRNA primer set can significantly influence the analysis of microbiota diversity and composition. Apart from a recent study evaluating the female urobiome ( Hoffman et al., 2021 ), similar studies for urinary microbiota profiling are lacking. As reviewed by Cumpanas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on species cultured from the female urobiome and using an in silico approach with 16S rRNA sequences retrieved from the SILVA database, Hoffman et al. (2021) showed that taxonomic assignment algorithms, 16S rRNA databases, and the choice of 16S rRNA hypervariable regions influence the taxonomic profiles of female urine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations